Suicidal Behavior : assessment of people-at-risk - Mandal, Manas K. (London : Sage, 2010)
Suicide is the second leading cause of death in the 10- to 19-year-old population in Oregon. The suicide rate has increased more than five-fold in the last three and one-half decades. This trend can be reversed by developing an understanding of the characteristics, behaviors, and events associated with suicide in at-risk youth. The Youth Risk Behavior Survey (YRBS) is one tool available to identify suicidal ideation and behavior. Fifty high schools were randomly selected to participate in the survey. This report describes demographic, environmental, and behavioral characteristics associated with suicide attempts. Survey results determined that suicide is a persistent problem among Oregon's youth. Among those who attempt suicide, there is a spectrum of desires, from cries for help to death. Many youth are ambivalent about ending their lives, and would rather live if a solution could be found. There is a continuum of self-destructiveness that can be measured in adolescents, and these behaviors and characteristics relate to premature adult mortality. The best individual behavioral characteristics for identifying high school students at risk of making suicide attempts are injection drug use, frequent use of inhalants, tobacco or cocaine, and multiple pregnancies. Appendixes include: (1) acknowledgement of participating schools; (2) YRBS questionnaire; (3) risky behavior and the home environment; (4) statistics of suicide attempts and deaths, 1994-1996; and (5) school-based health centers. Ways to help prevent teen suicide and limitations of this study are discussed. (Contains 68 references, 13 figures, and 12 tables.) (JDM)
Includes index.
Microfiche.
Keywords: Suicidal behavior -- Risk factors -- Testing; Hurried Childhood; Numerical/Quantitative Data; Reports, Research; Tests/Questionnaires.